The Beginning, Not the End: On Continental Philosophy of Religion and Religious Studies - Onishi, Bradley B. ca. 20./21. Jh. (Journal of the American Academy of Religion, 2017)
Recently, scholars have reflected critically on the role of philosophy in the field of religious studies and the future of the subfield within the academic study of religion (see Crocket et al. 2014; Smith and Whistler 2010; Schilbrack 2014). One of the common elements of these reflections has been the concern on the part of philosophers of religion and their colleagues in the academic study of religion that philosophy of religion is in fact a thinly veiled form of theology that has been allowed to exist illegitimately in departments of religious studies. This concern is articulated forcefully in a recent set of publications, ominously titled The Ends of Philosophy of Religion (2013) and “The End of Philosophy of Religion?” (2014), wherein Timothy Knepper argues that philosophy of religion, both in its analytic and continental iterations, “has very little to offer” religious studies for two main reasons. First, “The content of reflection in philosophy of religion is usually either a fictionalized and rarified theism or the latest critical notion of some continental philosopher, not the historical religions of the world in their localized complexity and comparative diversity” (2013, 9). Second, philosophy of religion is either explicitly or implicitly theological: “Philosophy of religion can look more like philosophical theology—not a (relatively) religiously neutral examination of reason-giving in the religions of the world, but an overt apologetic for (or against) the reasonableness or value of some particular kind of religion” (2013, 9).1 In Knepper's view, both analytical and continental philosophy of religion—as they are currently practiced—are abstracted from lived religion and more often than not are forms of theological apologetics rather than a “neutral” evaluation of religious phenomena.